Management of Schneiderian Membrane Perforations during Sinus Augmentation Procedures: A Preliminary Comparison of Two Different Approaches - Barbu, Horia Mihail (J Clin Med, 2019)
Background: The aim of this study was to retrospectively analyze two different sealing techniques for sinus membrane perforations produced during sinus floor augmentation by a lateral approach. Methods: A total of 172 lateral-approach sinus floor augmentation surgeries were performed on 130 patients. Sixty-one membrane perforations (35%) were reported. Most of the perforations were caused by accidental membrane tearing and 16 (26%) were caused by deliberate incision for mucocele removal. In 31 perforation cases (51%), the Schneiderian membrane was sealed by suturing, while the remaining 30 cases (49%) were sealed using a low-resorption collagen membrane coverage. Results: Out of the 31 cases treated with a suture-sealing techniques, 26 (84%) were successful, presenting graft integration. Failure occurred in the other five (16%) cases. Out of the 30 perforations sealed with low-resorption collagen membranes, 28 (93%) presented successful graft integration, while two (7%) failed. Conclusions: Both surgical techniques yielded therapeutic success.